Digital Environment as a Means of Developing Aerospace Students’ Independent Work Skills at the University - Natalia M. PODPORINA; Svetlana V. SHELIKHOVA; Yanina I. VOYTALYANOVA (Communications of International Proceedings, 2021)
The article is devoted to one of the main trends in modern education system – digital education. The authors state the necessity for digital transformation of higher education system which has already been reflected in the new state standards of higher education for students of aerospace specialties. Moreover, this causes an objective need for the development of students’ independent work skills. A special electronic self-study course has been developed within the framework of the study of the foreign language discipline for the development of students’ independent work skills. The course covers the main topics provided by the program of the foreign language discipline for students of aerospace specialty and provides for both the development of all aspects of speech, and the possibility of improving students' independent work skills. The number of students enrolled for the course and successfully completed it in the period of 2018-2020 was analyzed. The analysis of the data obtained showed the growth of both the number of the students registered for the course and the number of the students successfully completed it. The results of the analysis proved the efficiency of the course for the development of aerospace students’ independent work skills and provided further basis for the research of the impact of digital transformation in higher education system on the development of other learning and teaching aspects.
Keywords: digital environment; higher education; foreign language; independent work skills; aerospace students; self-study course.